The Bamboo Greenhouse Technology For Hydroganic Plants with Independent Photovoltaic Energy in the Food Safety Program - Budiyanto, Hery; Setiawan, Aries Boedi; Haris, Munanto; Iqbal, Muhammad; Sonalitha, Elta (University of Merdeka Malang, 2020)
The development of the city has made a lot of agricultural land turned into residential land and other urban facilities so that agricultural land becomes increasingly narrow so that it can weaken the food safety program. Another way is needed to utilize narrow land in an effort to develop agricultural products, namely by farming and maintaining fish hydroganic. Hydroganic comes from the words